Cadaverine’s Functional Role in Plant Development and Environmental Response - Jancewicz, Amy L.; Gibbs, Nicole M.; Masson, Patrick H. (Frontiers in Plant Science, 2016)
Cadaverine derives from lysine in a pathway that is distinct from that of the other well-characterized ornithine- or arginine-derived polyamines. Despite a multitude of studies in bacterial systems, cadaverine has garnered little attention in plant research. Nonetheless, many plants have been found to synthesize it. For instance, the Leguminosae have been shown to produce cadaverine and use it as a precursor in the biosynthesis of quinolizidine alkaloids, secondary metabolites that are involved in insect defense and also display therapeutic pharmacological properties. Cadaverine is also present in the environment; it can be produced by rhizosphere and phyllosphere microbes. Markedly, exogenous cadaverine application causes alterations in root-system architecture. Previous research suggests cadaverine has a role in stress response, with groups reporting an increase in content upon exposure to heat, drought, salt, and oxidative stress. However, data regarding the role of cadaverine in stress response remains conflicted, as some plant systems show enhanced tolerance to stresses in its presence, while others show increased sensitivity to the same stresses. In this review, we summarize recent findings on the role of cadaverine in plant growth, development, and stress response. We also address the possible roles rhizosphere and phyllosphere microbes may play in the delivery of exogenous cadaverine near plant organs, and discuss our current understanding of the molecular pathways that contribute to cadaverine homeostasis and response in plants.